Kualitas dan Kesuksesan Implementasi Layanan E-Learning Berbasis Moodle dengan Menggunakan Expectation-Confirmation Model dan Delone and Mclean's Model - Aryanti Dyah Ayu Dwi Putranti; Admaja Dwi Herlambang; Mochammad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Based on the data obtained from the observation of four faculties in Brawijaya University that have utilized moodle-based e-learning, namely the Faculty of Agriculture (FP), the Faculty of Accounting (FIA), the Faculty of Agricultural Technology (FTP), and the Faculty of Computer Science (FILKOM). This research has purpose to know condition of quality and success of moodle based e-learning implementation. The research was conducted by using two models: Expectation-Confirmation Model to know the quality of e-learning implementation and DeLone & McLean model to know the success of e-learning implementation. ECM has four variables, namely perceived usefullness, confirmation, satisfaction, and continuance intention. DeLone & McLean model has six variables, namely system quality, information quality, service quality, use, user satisfaction, and net benefits. The data used were 148 respondents selected with stratified cluster sampling. Data collection techniques were conducted through an online questionnaire. The result of the data has been collected, service quality, and user satisfaction was high enough category, and other variables was high category. The recommendations given based on indicators of each variable that has a value below the total average, so it can improve the quality and success of e-learning implementation.